Investigating the factors that drive social commerce purchase intention amongst the millennials in South Africa - Kiza, Melikhaya (School of Management Studies, 2025)
Social media has become fundamental to companies, as well as consumers. Its existence has produced new opportunities and introduced options like ‘social commerce' whereby consumers and firms can sell goods and services on social media platforms. Due to the evolution of marketing from 1.0 to 4.0, there has been limited research about marketing 4.0 within social commerce. The current study aimed to assess marketing 4.0 dimensions and social commerce characteristics that have been under-studied - particularly how they affect millennial's purchase intentions in social commerce. A sample of 261 millennials was received from two different provinces Western Cape and Gauteng. The findings revealed that platform reputation, reviews, ratings, and product differentiation enhance trust and price. Moreover, trust shows no influence on purchase intention – and nor did brand image, brand integrity and brand identity. Findings from this study indicate that product differentiation, reviews and ratings, and platform reputation are the underlying reasons for trust and brand image are drivers of social commerce purchase intention. Thus, managers need to listen to consumers and produce individualised products to ensure unique and well differentiated offerings. Marketing practitioners should rather focus on using reputable social networks such as Facebook, Twitter and Instagram as key social commerce platforms for the purchase of products. Furthermore, as reviews and ratings are important for millennials, marketers should provide a good response to negative feedback. Lastly, managers in online communities should provide an excellent customer service as that will enhance customer service and lead to purchase intention.